(untitled) (AYUSHDHARA, 2017)
A healthy child is wealth of a nation. Future of a nation depends on health status of its children and youth. In present era, due to change in lifestyles, environment and food habits, many new challenges and diseases are arising in front of medical experts. Among these many of the diseases are preventable. In pediatric age group, right from the conception to adolescence there are many factors that affect fetus or child adversely. By eliminating these factors, we can prevent many diseases in offspring or child. Kaumarbhritya physician has role right from the time of conception to adolescent. It is need of hour that Kaumarbhritya physician should come forward to serve the society. Principles like Garbhadharana with Shudha Shukra and Shonita, Masanumasika Garbhini Paricharya, Navjata Shishu Parichariya, various Samskara’s, Sadvrita Palana and Achara Rasayan have great importance in child growth and development and also essential for obtaining a healthy progeny. These principles prevent from many diseases and also have scientific validity. For example a healthy mother who follows proper Masanumasika Garbhini Paricharya and devoid of exposure from teratogen, gives birth to a healthy child. Navjata Shishu Parichariya helps newborn in overcoming the stress faced during process of birth and helps in adjusting in external environment with ease, along with prevention from many complications like birth asphyxia etc. Samskara’s are one of the important tolls for early assessment of growth and developmental disorders and also helps in better growth and development by improving immunity and timely addition of weaning food for providing additional nutrients and micronutrients. In present era there are increased antibiotic resistances and more number of populations is effecting with infectious and autoimmune diseases due to poor immunity. By maintaining health we can prevent such conditions.